2020
DOI: 10.1002/lt.25795
|View full text |Cite
|
Sign up to set email alerts
|

Livers From Pediatric Donation After Circulatory Death Donors Represent a Viable and Underutilized Source of Allograft

Abstract: Despite increased numbers of donation after circulatory death (DCD) donors, pediatric DCD livers are underused. To investigate possible reasons for this discrepancy, we conducted a retrospective cohort study using 2 data sets from the Organ Procurement and Transplantation Network for all deceased liver donors and for all recipients of DCD liver transplants from March 8, 1993, to June 30, 2018. Pediatric (0‐12 years) and adolescent (13‐17 years) DCD donors were compared with those aged 18‐40 years. We found tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 42 publications
(62 reference statements)
0
6
0
Order By: Relevance
“…In context of the potential donor and recipient age mismatch, there is a general reluctance to use DCD liver grafts for pediatric recipients. 90,91 Hwang et al 91 showed equal graft survival rates in pediatric DCD and DBD recipients in the UNOS cohort from very young donors with an age of 11 and 12 y, respectively. DCD liver grafts are also more frequently transplanted into older children.…”
Section: Methodsmentioning
confidence: 99%
“…In context of the potential donor and recipient age mismatch, there is a general reluctance to use DCD liver grafts for pediatric recipients. 90,91 Hwang et al 91 showed equal graft survival rates in pediatric DCD and DBD recipients in the UNOS cohort from very young donors with an age of 11 and 12 y, respectively. DCD liver grafts are also more frequently transplanted into older children.…”
Section: Methodsmentioning
confidence: 99%
“…24 Despite an increasing number of cDCD donors, an alarming rate of nonrecovery and discarded livers from pediatric cDCD donors have been published. 25 A recent United Network for Organ Sharing national registry study showed that cDCD accounted for <5% (443 from 8967) of livers transplanted from pediatric donors. 23 Most large series of pediatric cDCD donors have shown that livers are massively allocated into adult recipients.…”
Section: Discussionmentioning
confidence: 99%
“…23 Most large series of pediatric cDCD donors have shown that livers are massively allocated into adult recipients. 23,25 Nevertheless, it has been recently observed that pediatric recipients of livers from cDCD donors have better allograft and patient survival than adult recipients. 24,26 Liver acceptance in our study was high, with 85% livers recovered and transplanted and no livers discarded during the recovery procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, outcomes from pediatric DCD donors also have excellent outcomes. Little et al 20 found that although pediatric DCD livers are procured at a lower rate than their adult counterparts, the outcomes are comparable. In addition, recovery rates of younger donors (0–12 years) were significantly lower than donors aged 13‐17 years.…”
Section: Livermentioning
confidence: 99%